Study on regeneration performance of carbon fluoride adsorbent in SF6 gas - Cheng Wei; Zhu Feng; Hang Chen; Xu ZhengJie (E3S Web of Conferences, 2023)
To study the regeneration of CF-100 type microcrystalline material after adsorbing carbon fluorides in SF6, an experimental device was built that can achieve both vacuum desorption of carbon fluorides and auxiliary heating to promote vacuum desorption of carbon fluorides. Thermogravimetric analyzer and Fourier transform infrared spectrometer were used to analyze the optimal treatment temperature and time of regeneration technology for promoting vacuum desorption of fluorocarbon by auxiliary heating. A comparative study was conducted on the two regeneration techniques mentioned above by analyzing the relationship between adsorption performance and the number of regenerations. The regeneration effects were also validated by using a specific surface area tester to examine the test data. The results demonstrate that desorption of fluorocarbons from CF-100 microcrystalline material is more efficient using a vacuum desorption method aided by auxiliary heating, as opposed to pure vacuum desorption. The CF-100 type of microcrystalline material achieves the best desorption effect when heated to 300°C with an auxiliary heating duration of 2 h, with an activation energy of 293.933 KJ/mol. After activation, CF-100 microcrystalline materials exhibit stable adsorption and desorption performance for decarbonization and possess excellent recyclability.